Increased accuracy of species lists developed for alpine lakes using morphology and cytochrome oxidase I for identification of specimens. (18th June 2013) - Deiner, Kristy; Knapp, Roland A.; Boiano, Daniel M.; May, Bernie
Abstract: The first step in many community ecology studies is to produce a species list from a sample of individuals. Community ecologists now have two viable ways of producing a species list: morphological and barcode identification. In this study, we compared the taxonomic resolution gained by a combined use of both methods and tested whether a change in taxonomic resolution significantly impacted richness estimates for benthic macroinvertebrates sampled from ten lakes in Sequoia National Park, USA. Across all lakes, 77 unique taxa were identified and 42% (32) were reliably identified to species using both barcode and morphological identification. Of the 32 identified to species, 63% (20) were identified solely by comparing the barcode sequence from cytochrome oxidase I to the Barcode of Life reference library. The increased resolution using a combined identification approach compared to identifications based solely on morphology resulted in a significant increase in estimated richness within a lake at the order, family, genus and species levels of taxonomy ( P  < 0.05). Additionally, young or damaged individuals that could not be identified using morphology were identified using their COI sequences to the genus or species level on average 75% of the time. Our results demonstrate that a combined identification approach improves accuracy of benthic macroinvertebrate species lists in alpine lakes and subsequent estimates of richness. We encourage the use of barcodes for identification purposes and specifically when morphology is insufficient, as in the case of damaged and early life stage specimens of benthic macroinvertebrates.